PERBEDAAN PENGUASAAN KOSAKATA ANAK PRA-SEKOLAH - Dwi Astuti Irenaningtyas; Ratna Wulan (Jurnal Psikologi, 2004)
The purpose of this study is to find out the differences in vocabulary size among pre-school children by means of comparing those who are used to listening storybooks read out by an adult to those who are not. The hypothesis is that the children who are well-acquainted to listening storybooks read out by an adult seize higher vocabulary size. The research involves 65 pre-school students between 5 years and 6 months to 6 years and 10 months of age, both male and female, selected from Pamardisiwi Kindergarten in Yogyakarta. There are 31 students who get to listen to storybooks read out by an adult in a regular basis, while the rest 34 are conditioned otherwise. The Peabody Picture Vocabulary Test (PPVT) Form A was applied to measure the vocabulary size, and in order to asses children’s activities in listening to storybooks read out by an adult, parents are required to write a one week journal. Independent-samples t-test analysis was used as a statistical method. The result of the study is t = 6.913 (p